Synthesis and Characterization of Modified Cellulose Acetate Propionate Nanocomposites via Sol-Gel Process - Patrycja Wojciechowska; Zenon Foltynowicz; Marek Nowicki (Journal of Spectroscopy)
In this study novel organic-inorganic hybrid nanocomposites were synthesized from modified cellulose acetate propionate (MCAP) via sol-gel reaction at ambient temperature. The inorganic phase was introduced in situ by hydrolysis-condensation of tetraethoxysilane (TEOS) in different concentrations, under acid catalysis, in the presence of organic polymer dissolved in acetone. The chemical modification of CAP was monitored by infrared spectroscopy (IR). The nanocomposites structure was characterized by IR analysis and solid state 29Si NMR studies. The spectral data revealed that organic and inorganic phases are linked through covalent bound. Surface morphology of the samples and the degree of dispersion of inorganic phase in the polymer matrix were investigated using atomic force microscopy (AFM) and scanning electron microscopy (SEM). The actual incorporation of the inorganic component into the hybrid nanocomposites was deducted from the residual weight according to thermogravimetric analysis (TGA).